PUBLIC POLICIES AND ENVIRONMENTAL PROTECTION: ANALYSIS OF ENVIRONMENTAL LEGISLATION APPLICABLE TO A RIVER BASIN IN SOUTHEAST BRAZIL - Machado, Fernando Henrique [UNESP]; Fengler, Felipe Hashimoto [UNESP]; Medeiros, Gerson Araujo de [UNESP] (Escola Superior Dom Helder Camara, 2019)
The Jundiai-Mirim River Basin (BH-JM) is the most important source of public water supply in Jundiai (SP). In the last decades, the accentuated economic and population growth has caused countless externalities, such as environmental degradation. For this reason, studies related to environmental public policies represent important analytical instruments for management purposes in order to evaluate the effectiveness of environmental protection by the State. Thus, this study aimed to identify and discuss public environmental policies (of legal nature) related to the Jundiai-Mirim River Basin (BH-JM). For this purpose, a bibliographical and documentary research was used, along with a historical-descriptive approach in order to analyze the state and municipal environmental legislation. We identified 14 public regulatory applicable to BH-JM: 9 municipals (8 Laws and 1 Resolution); and 5 state (1 Law, 3 Decrees, and I Resolution). The analysis showed that Jundiai has a broad legal framework; nevertheless, there was limited legal effectiveness in its implementation when the established requirements are compared with existing environmental studies. For this reason, the need for more government intervention and community participation was observed, in order to ensure effective compliance with the established laws. Furthermore, management guidelines were proposed in to subsidize better management of the river basin.
Keywords: Antropogenic Pressure; Environmental legislation; Jun-diai-Mirim; PCJ River Basins